Multiple Kernel Based Region Importance Learning for Neural Classification of Gait States from EEG Signals - Zhang, Yuhang; Prasad, Saurabh; Kilicarslan, Atilla; Contreras-Vidal, Jose L. (Frontiers in Neuroscience, 2017)
With the development of Brain Machine Interface (BMI) systems, people with motor disabilities are able to control external devices to help them restore movement abilities. Longitudinal validation of these systems is critical not only to assess long-term performance reliability but also to investigate adaptations in electrocortical patterns due to learning to use the BMI system. In this paper, we decode the patterns of user’s intended gait states (e.g., stop, walk, turn left and turn right) from scalp electroencephalography (EEG) signals and simultaneously learn the relative importance of different brain areas by using the multiple kernel learning (MKL) algorithm. The region of importance (ROI) is identified during training the MKL for classification. The efficacy of the proposed method is validated by classifying different movement intentions from two subjects – an able-bodied and a spinal cord injury (SCI) subject. The preliminary results demonstrate that frontal and frontal-central regions are the most important regions for the tested subjects performing gait movements, which is consistent with the brain regions hypothesized to be involved in the control of lower-limb movements. However, we observed some regional changes comparing the able-bodied and the SCI subject. Moreover, in the longitudinal experiments, our findings exhibit the cortical plasticity triggered by the BMI use, as the classification accuracy and the weights for important regions - in sensor space - generally increased, as the user learned to control the exoskeleton for movement over multiple sessions.